Support in Clinical Settings as Perceived by Nursing Students in Iran: A Qualitative Study - Joolaee; Ashghali Farahani; Jafarian Amiri; Varaei (Kashan University of Medical Sciences, 2016)
Background Although support is one of the most substantial needs of nursing students during clinical education, it is not clearly defined in the literature. Objectives The current study aimed to explore the concept of support in clinical settings as perceived by nursing students. Materials and Methods A qualitative content analysis was used to explore the meaning of student support in clinical settings. A purposive sampling with maximum variation was used to select the participants among bachelor nursing students in the nursing school of Babol University of Medical Sciences in the north of Iran. Semi-structured interviews were conducted to gather the perceptions and experiences of seventeen nursing students. Conventional content analysis was applied to analyze the data. Results In the current study, the main theme, nurturance, was emerged with seven subthemes of humanistic behavior with the student, respectful communication with students, accepting the student in the clinical setting, sustaining confidence, need based supervision, accepting the profession in the society and empowerment. Conclusions Nursing students support in the clinical education requires a nurturing care; a care that leads to the sense of worthiness and respectability in students and contributes to the improvement of their clinical abilities.